2006
DOI: 10.2166/ws.2006.807
|View full text |Cite
|
Sign up to set email alerts
|

Development and dissemination of Kanchan™ Arsenic Filter in rural Nepal

Abstract: In the rural Terai region of Nepal, many tubewell drinking water sources are microbially and/or arsenic contaminated and consequently, millions lack access to “safe” water. Those who drink contaminated water may suffer from preventable water-borne diseases such as diarrhoea, stunting, skin lesions, and cancer. To combat this problem, a team comprising researchers from Massachusetts Institute of Technology (MIT), together with two local partners, Environment & Public Health Organization (ENPHO), and Rural W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
94
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(106 citation statements)
references
References 0 publications
0
94
0
Order By: Relevance
“…During the past two decades, great efforts have been made to develop Fe 0 filters for use in decentralized water supply systems in developing countries, including Argentina, Bangladesh, Cambodia, Cameroon, Chile, India, Nepal and Vietnam [39,40,64,66,72,[78][79][80][81][82][83][84][85][86]. Several Fe 0 filters exist and were also developed/optimized by scientists from many institutions worldwide, including the Massachusetts Institute of Technology [78,79], George Mason University [81] and the Swiss Federal Institute of Aquatic Science and Technology [86,87].…”
Section: Historical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past two decades, great efforts have been made to develop Fe 0 filters for use in decentralized water supply systems in developing countries, including Argentina, Bangladesh, Cambodia, Cameroon, Chile, India, Nepal and Vietnam [39,40,64,66,72,[78][79][80][81][82][83][84][85][86]. Several Fe 0 filters exist and were also developed/optimized by scientists from many institutions worldwide, including the Massachusetts Institute of Technology [78,79], George Mason University [81] and the Swiss Federal Institute of Aquatic Science and Technology [86,87].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Several Fe 0 filters exist and were also developed/optimized by scientists from many institutions worldwide, including the Massachusetts Institute of Technology [78,79], George Mason University [81] and the Swiss Federal Institute of Aquatic Science and Technology [86,87].…”
Section: Historical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, very efficient Fe [31][32][33][34] but were abandoned because of service lives of only 6 to 24 weeks [35][36][37]. Hussam [37] reported that 3-Kolshi filters were "highly functional, but not sustainable" as the filters experienced permeability loss after 3 to 6 months.…”
mentioning
confidence: 99%
“…Some extremely economical devices have already been conceived for developing-world situations, which can be manufactured immediately using sustainable resources, many of which are available at the point of use. Good examples are the terracotta filtration devices developed by Potters for Peace, which can be made by local workers 8 , and the Kanchan arsenic filters made from very basic materials: iron nails, brick, sand and gravel 9 . But more could be done to apply science in the development of lowtech filters; even more pressing is the need for cheap and easy-to-operate devices to identify contaminated waters and quantify levels of pollution, to ascertain the degree of danger from its consumption.…”
mentioning
confidence: 99%